Expertise in Tool Use Promotes Tool Embodiment. (3rd June 2021) - Weser, Veronica U.; Proffitt, Dennis R.
Abstract: Body representations are known to be dynamically modulated or extended through tool use. Here, we review findings that demonstrate the importance of a user's tool experience or expertise for successful tool embodiment. Examining expert tool users, such as individuals who use tools in professional sports, people who use chopsticks at every meal, or spinal injury patients who use a wheelchair daily, offers new insights into the role of expertise in tool embodiment: Not only does tool embodiment differ between novices and experts, but experts may experience enhanced changes to their body representation when interacting with their own, personal tool. The findings reviewed herein reveal the importance of assessing tool skill in future studies of tool embodiment.